Synthesis of polyaniline modified with palm oil based Alkyd as counter electrode in solar cell application / Mariam Fadzlina Ramli - Mariam Fadzlina , Ramli (2020)
Presently, shortage of sustainable and environmental friendly energy resources has become an important global concern. Dye-sensitized solar cell (DSSC) has widely been used as a clean energy conversion device that can solve this problem. Platinum (Pt) has commonly been used as counter electrode (CE) in DSSC due to its good redox property. However, Pt is expensive and could be easily corroded in tri-iodide solution. Recently, polyaniline (PAni) has shown promising performance in DSSC, but PAni exhibit poor adhesion on fluorine-doped tin oxide (FTO) substrate. In this study, an environmental friendly CE was developed by modifying PAni using titanium dioxide (TiO2) and a palm oil-based (POB) alkyd to improve both the electrocatalytic activity and adhesion on FTO without using any toxic organic solvent like m-Cresol. A series of PAni and PAni-TiO2 with different TiO2 content (10%, 20% and 40%) were synthesized via chemical oxidative polymerization. POB alkyd was synthesized through alcoholysis and esterification reactions. Chemical structures of PAni, PAni-TiO2 and POB alkyd were confirmed by FTIR, UV-Vis, XRD and 1H NMR analyses. Result obtained showed that PAni exist as emeraldine salt phase with electrical conductivity of 1.23×103 to 1.31×103 Scm-1. The preparation of PAni modified with POB alkyd (PAni/Alkyd) films were investigated by different PAni:Alkyd ratios (1:0.5, 1:0.75 and 1:1), different acid number (AN) of POB alkyd (5.66, 14.74 and 17.60 mgKOH/g) and different reactive diluents such as methyl acrylate (MA), methyl methacrylate (MMA) and cyclohexyl methacrylate (CMA) under UV curing method. Among all PAni/Alkyd films, PAni/Alkyd using ratio 1:0.5 with alkyd having AN of 5.66 mgKOH/g and CMA as diluent give the lowest curing time of 5 min to give adhesion of 5B. Besides, PAni-TiO2 modified with POB alkyd (PAni-TiO2/Alkyd) films were prepared using similar ratio as discussed earlier. The results showed that all PAni/Alkyd and PAni-TiO2/Alkyd films exhibit high conductivity range of 6.11×102 to 6.49×102 Scm-1 with good adhesion on FTO substrate. The adhesion of PAni on FTO is significantly contributed by the reactive C=C of the POB alkyd that undergo crosslinking in the PAni/Alkyd coating during UV curing. Conductivity and adhesion are two main crucial factors that will contribute to high power conversion efficiency (PCE) of DSSC. In this research, the fabrications of DSSC were prepared using TiO2 photoanode, ruthenium dye, PAni/Alkyd and PAni-TiO2/Alkyd as CE and iodolyte AN50 electrolyte. The highest PCE was shown by PAni/Alkyd with 0.60% while PAni-TiO2/Alkyd showed lower PCE range of 0.20% to 0.30%. This is because PAni/Alkyd possessed higher conductivity of 6.49×102 Scm-1 compared with PAni-TiO2/Alkyd (6.11×102 to 6.32×102 Scm-1). As a result, an environmentally POB alkyd modified PAni as CE with high electrical conductivity of 6.11×102 to 6.49×102 Scm-1, excellent adhesion of 5B and moderate PCE of 0.20% to 0.60% in DSSC were successfully obtained. This research results confirmed that PAni modified with POB alkyd can be potentially applied as cost-effective and environmental friendly materials used for DSSC study.